The impact of climate change on incomes and convergence in Africa. (February 2020) - Baarsch, Florent; Granadillos, Jessie R.; Hare, William; Knaus, Maria; Krapp, Mario; Schaeffer, Michiel; Lotze-Campen, Hermann
Highlights: We estimate climate-induced losses in Africa by Accounting for the dimensions of risks: exposure, vulnerability and hazards. With losses up to 15 percent of GDP per capita growth, African economies are poorly adapted to their climatic conditions. Western and Eastern African countries are projected to be the most affected countries on the continent. Inequalities between countries are projected to widen as a consequence of climate change. Solutions include raising mitigation ambition, scaling-up adaptation efforts and special treatments for the most vulnerable. Abstract: Climate change is projected to detrimentally affect African countries' economic development, while income inequalities across economies is among the highest on the planet. However, it is projected that income levels would converge on the continent. Hitherto there is limited evidence on how climate change could affect projected income convergence, accelerating, slowing down, or even reversing this process. Here, we analyze convergence considering climate-change damages, by employing an economic model embedding the three dimensions of risks at the country-level: exposure, vulnerability and hazards. The results show (1) with historical mean climate-induced losses between 10 and 15 percent of GDP per capita growth, the majority of African economies are poorly adapted to their current climatic conditions, (2) Western and Eastern African countries are projected to be the most affected countries on the continent and (3) As a consequence of these heightened impacts on a number of countries, inequalities between countries are projected to widen in the high warming scenario compared to inequalities in the low and without warming scenarios. To mitigate the impacts of economic development and inequalities across countries, we stress (1) the importance of mitigation ambition and Africa's leadership in keeping global mean temperature increase below 1.5 °C, (2) the need to address the current adaptation deficit as soon as possible, (3) the necessity to integrate quantitatively climate risks in economic and development planning and finally (4) we advocate for the generalization of a special treatment for the most vulnerable countries to access climate-related finance. The analysis raises issues on the ability of African countries to reach their SDGs targets and the potential increasing risk of instability, migration across African countries, of decreased trade and economic cooperation opportunities as a consequence of climate change – exacerbating its negative consequences.